Increased FOXM1 Expression was Associated with the Prognosis and the Recruitment of Neutrophils in Endometrial Cancer - Jing Chen; Pusheng Yang; Shaojing Li; Yichen Feng (Journal of Immunology Research)
Background. Although the biological functions of Forkhead box protein M1 (FOXM1) were explored in a variety of cancer, to date, however, little attention has been paid to the situation of FOXM1 in EC endometrial cancer (EC). Method. Bioinformatics analysis, including GEPIA, TIMER, cBioPortal, LinkedOmics, and STRING were used to analyze the FOXM1 gene expression, genetic alteration, and immune cell infiltration in EC. IHC staining, qPCR, cell viability, and migration assay were applied to identify the functions of FOXM1 in EC. Results. FOXM1 was highly expressed in EC tissues and closely correlated with the prognosis of EC patients. FOXM1 knockdown inhibited EC cell proliferation and invasion as well as migration. FOXM1 genetic alteration was verified in EC patients. Coexpression network of FOXM1 indicated that it had roles in the EC cell cycle and the infiltration of immune cells in EC. Furthermore, bioinformatic and immunohistochemical analysis indicated that FOXM1 induced the increased CD276 expression and also enhanced the neutrophil recruitment in EC. Conclusion. Our present study discovered a novel role of FOXM1 in EC, suggesting FOXM1 could be treated as a potential prognostic biomarker and immunotherapeutic target in EC diagnosis and treatment.